The Analysis of Student Learning Motivation in Communication Education Courses in The Islamic Religion Study Program, Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara - Tsania, Ulfa; Syahril, Muhammad; Ariani , Rini (Journal of General Education Science, 2023)
In higher education, especially at the Muhammadiyah University of North Sumatra, there are various kinds of platforms that can be used to develop students' interests, talents and creativity. One of the faculties at the Muhammadiyah University of North Sumatra is the Faculty of Islamic Religion. Student success in learning on campus can be seen through learning achievements shown in the Achievement Index (IP). Learning achievement is a point of attention that becomes a benchmark for student success in their learning process over a certain period of time. Students with high learning achievements can be interpreted as having been successful in their studies. Student success in learning achievement is influenced by several things, one of which is the student's activeness, especially communication science. A student must have communication skills such as public speaking, students can develop and apply the skills they have and can also train leadership skills. However, if you want to take part in the social field, communication science is needed everywhere. Speaking skills support students in becoming content creators, leaders and others, to increase their particular attractiveness.